Deficiency of Pkc1 activity affects glycerol metabolism in Saccharomyces cerevisiae - Gomes, K. N. (2005)
Protein kinase C is apparently involved in the control of many cellular systems: the cell wall integrity pathway, the synthesis of ribosomes, the appropriated reallocation of transcription factors under specific stress conditions and also the regulation of N-glycosylation activity. All these observations suggest the existence of additional targets not yet identified. In the context of the control of carbon metabolism, previous data demonstrated that Pkc1 p might play a central role in the control of cellular growth and metabolism in yeast. In particular, it has been suggested that it might be involved in the derepression of genes under glucose-repression by driving an appropriated subcellular localization of transcriptional factors, such as Mig1 p. In this work, we show that pkc1∆ mutant is unable to grow on glycerol because it cannot perform the derepression of GUT1 gene that encodes for glycerol kinase. Additionally, active transport is also partially affected. Using this phenotype, we were able to isolate a new pkc1∆ revertant. We also isolated two transformants identified as the nuclear exportin Msn5 and the histone deacetylase Hos2 extragenic suppressors of this mutation. Based on these results, we postulate that Pkc1 p may be involved in the control of the cellular localization and/or regulation of the activity of nuclear proteins implicated in gene expression.